2017
DOI: 10.1200/jco.2016.71.7439
|View full text |Cite|
|
Sign up to set email alerts
|

Participant-Reported Symptoms and Their Effect on Long-Term Adherence in the International Breast Cancer Intervention Study I (IBIS I)

Abstract: PurposeTo assess the role of participant-reported symptoms on long-term adherence to preventive therapy in the United Kingdom sample of the International Breast Cancer Intervention Study (IBIS-I). IBIS-I was a randomized controlled trial that investigated the effectiveness of tamoxifen in reducing the risk of breast cancer among women at increased risk of the disease.Participants and MethodsWomen were randomly assigned to tamoxifen versus placebo (20 mg/day; n = 4,279). After 456 exclusions, 3,823 women were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…A prompt symptom management and safety reassurance by the physician helped women to be motivated to adhere to the treatment. The recent analysis from the IBIS I study showed a higher drop-out rates in the tamoxifen arm, but the adherence did not differ between tamoxifen and placebo considering the overall reported symptoms (9). This leads to a further issue, i.e., the nocebo effect, that might be crucial in a preventive treatment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A prompt symptom management and safety reassurance by the physician helped women to be motivated to adhere to the treatment. The recent analysis from the IBIS I study showed a higher drop-out rates in the tamoxifen arm, but the adherence did not differ between tamoxifen and placebo considering the overall reported symptoms (9). This leads to a further issue, i.e., the nocebo effect, that might be crucial in a preventive treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Menopausal symptoms (hot flashes and night sweats) were a main reason for full-dose tamoxifen treatment withdrawal in the IBIS I trial (9). Maintaining a high QoL is therefore crucial to implement therapeutic prevention on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Song and coworkers ( Song et al . 2001 ) reported that long-term estrogen deprivation leads to estrogen-induced apoptosis in LTED breast cancer cell population in vitro .…”
Section: Evolution Of Acquired Resistance In Prostate and Breast Cancmentioning
confidence: 99%
“…Laboratory studies of acquired resistance to antihormone therapies ( Wolf & Jordan 1993 , Yao et al . 2000 , Song et al . 2001 ) opened the door to understanding the ‘carry over’ effect of long-term adjuvant antiestrogen therapy that decreases mortality after adjuvant therapy is stopped ( Fisher et al .…”
Section: An Approach To Global Health Care Maintenance In Prostate Anmentioning
confidence: 99%
See 1 more Smart Citation